#TITLE_ALTERNATIVE# - BARRY RAHMATULLAH (NIM 20807004), HADI
Graduation is smoothing process. One of its applications is mortality data smoothing. A common method used is Whittaker graduation. This method is a weighted regression, so that graduation outcome will largely depend on the weight used. If it used negative weight, than mortality level, which is a probability, is possible to have a negative value. To anticipate this, other method is used not only weighing one value, in this case mortality level, but it is a weighted average of two values. That graduation is called Bayesian Graduation.